2022
DOI: 10.4132/jptm.2022.08.22
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of BRAF VE1 immunohistochemistry in non–small cell lung cancers: a multi-institutional study by 15 pathologists in Korea

Abstract: Background: Next-generation sequencing (NGS) is an approved test to select patients for BRAF V600E targeted therapy in Korea. However, the high cost, long turnaround times, and the need for sophisticated equipment and skilled personnel limit the use of NGS in daily practice. Immunohistochemistry (IHC) is a rapid and relatively inexpensive assay available in most laboratories. Therefore, in this study, we evaluate the usefulness of BRAF VE1 IHC in terms of predictive value and interobserver agreement in non-sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similar results were shown by Hofman et al, suggesting that VE1 staining is a rapid, specific and very sensitive method [ 23 ]. In addition, Chang et al reported that VE1 immunohistochemistry showed almost perfect interobserver agreement, suggesting that this could be a screening test for BRAF mutation [ 24 ]. In present study, BRAF V600E mutated cases showed diffuse (100% of proportion) positivity, though the intensity was heterogeneous in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were shown by Hofman et al, suggesting that VE1 staining is a rapid, specific and very sensitive method [ 23 ]. In addition, Chang et al reported that VE1 immunohistochemistry showed almost perfect interobserver agreement, suggesting that this could be a screening test for BRAF mutation [ 24 ]. In present study, BRAF V600E mutated cases showed diffuse (100% of proportion) positivity, though the intensity was heterogeneous in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, 4 µm thick FFPE tissue sections were deparaffinized and rehydrated using a xylene and alcohol solution. We used an automated instrument (BOND-MAX immunostainer; Leica Biosystems, Deer Park, IL, USA) with a biotin-free polymeric horseradish peroxidase-linker antibody conjugate system (BOND Polymer Intense Detection System; Leica Biosystems) [33][34][35][36]. After antigen retrieval, endogenous peroxidases were quenched with hydrogen peroxide.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue sections from the corresponding formalin-fixed, paraffin-embedded blocks were mounted onto SuperFrost Plus Microscope Slides (Thermo Fisher Scientific, Waltham, MA, USA), deparaffinized in xylene, and then rehydrated using an ethanol gradient. Immunohistochemical staining was carried out using a Bond-Max automated immunostainer (Leica Biosystems, Lincolnshire, IL, USA) and a Bond Polymer Refine Detection System (Leica Biosystems), as described previously (11,30,(35)(36)(37)(38)(39). Following antigen retrieval, the slides were incubated with a primary antibody against L1CAM (dilution 1:100, clone EPR18998, Abcam, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%